Nutrients in Australian agro-industrial residues: production, characteristics and mapping. Issue 2 (2nd April 2016) - Mehta, Chirag; Tucker, Robyn; Poad, Glenn; Davis, Rod; McGahan, Eugene; Galloway, Justin; O'Keefe, Michael; Trigger, Rachel; Batstone, Damien
ABSTRACT: Australia is a net food exporter, but relies heavily on imported agricultural nutrients. There is scope to recycle nutrients from agro-industrial residues, but this has not been assessed in detail. The assessment reported identified significant potential for nitrogen, phosphorus and potassium to be recovered from different Australian agro-industrial residues. Suitable sources of residues were cattle feedlots, piggeries, poultry (layers), poultry (meat), sugar cane processing, meat processing, dairies, coal mining, milk processing, fish processing, urban waste and electricity generation. Significant nitrogen, phosphorus and potassium sources were municipal waste, sugarcane processing, cattle feedlots and sewage wastewater. A total of 246 kt N, 88 kt P, and 359 kt K was produced as residues in 2010, representing 23% of N and P, and >100% of K in relation to the annual national agricultural consumption. Australian agro-industrial nutrient source–sink maps revealed that the best potential residual nutrients sources were intensive livestock facilities, which are generally located within 200 km of grain-producing areas. However, due to existing markets or inexpensive disposal sinks in Australia, there is a limited availability of these residues for practical use. This may change as the value and/or demand of nutrients increases in the future.